Consolidation of flame hydrolysis deposited silica with a 9.3 µm wavelength CO2 laser. Issue 15 (1st July 2018) - Gow, P.C.; Jantzen, A.; Boyd, K.; Simakov, N.; Daniel, J.; Gray, A.C.; Gates, J.C.; Shardlow, P.C.; Smith, P.G.R.; Holmes, C.
Abstract : Consolidation of flame hydrolysis deposition silica soot with a 9.3 µm CO2 laser has been demonstrated. A range of laser parameters were investigated and the surface roughness of the resulting silica layers were characterised with a stylus profiler and white light interferometer. The surface roughness parameters were Ra = 68.9 nm, Rq = 83.8 nm perpendicular to the trajectory of the translated laser beam for a speed of 300 mm s −1 and an average laser power of 42.5 W, and Ra = 29.5 nm, Rq = 36.18 nm along the trajectory of the translated laser beam for a speed of 250 mm s −1 and an average laser power of 35.8 W.